Aging, mobility impairments and subjective wellbeing - Freedman, Vicki A.; Carr, Deborah; Cornman, Jennifer C.; Lucas, Richard E. (Disability and health journal, 2017)
Wellbeing is often described as U-shaped over the life course, suggesting an apparent paradox that wellbeing remains high at older ages despite increases in impairments. We explore associations among age, lower body impairments—one of the most common late-life impairments—and three measures of wellbeing: life satisfaction, emotional wellbeing and somatic wellbeing. We hypothesize that age effects are positive, become stronger once lower body impairments are controlled, and are concentrated among those who have maintained their mobility. Net of confounding factors, we hypothesize that lower body impairments are associated with worse wellbeing and these effects diminish with advancing age. We analyze the 2013 Disability and Use of Time supplement to the Panel Study of Income Dynamics (N = 1607 adults ages 60 and older). We estimate nested regression models that include age, severity of lower body impairments and confounding demographic, psychological, and socioeconomic factors and activities; test age-impairment interactions; and estimate age- and impairment-stratified models. Positive age effects were observed after controlling for lower body impairments for life satisfaction (β = 0.90; p < 0.05), although statistical significance weakened (p = 0.07) in fully adjusted models. For emotional wellbeing, adjusted age effects were negative (β = −0.05; p < 0.05) and were concentrated among those with limitations (β = −0.14; p < 0.01). For all three outcomes, severity of impairments reduced wellbeing in adjusted models. These effects were strongest for somatic wellbeing, especially for 65–74 year olds. Our study challenges the notion that wellbeing is U-shaped throughout the life course and underscores the critical role of mobility across wellbeing domains in later life.